2005
DOI: 10.1002/jgm.804
|View full text |Cite
|
Sign up to set email alerts
|

Genomic sequence correction by single‐stranded DNA oligonucleotides: role of DNA synthesis and chemical modifications of the oligonucleotide ends

Abstract: We show that, on a chromosomal level, the orientation of the replication fork towards the targeted locus is not central in the strand bias of ssODN-based targeted sequence correction. We demonstrate the importance of accessible ssODN ends for sequence alteration. Finally, we provide evidence for the involvement of DNA synthesis in the process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
69
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(79 citation statements)
references
References 40 publications
9
69
1
Order By: Relevance
“…30,[41][42][43][44][45][46] Largely, mechanistic studies have utilized a mutated eGFP gene as the target and a functional eGFP is produced if the gene is repaired; then, the corrected cells express eGFP and display green fluorescence. In the standard model system, a single copy of the eGFP gene with a single base mutation -TAC → TAG -generating a stop codon has been stably integrated in the sequence of HCT116 cells.…”
Section: Recovery and Proliferation Of Genetically Modified Cancer Cellsmentioning
confidence: 99%
“…30,[41][42][43][44][45][46] Largely, mechanistic studies have utilized a mutated eGFP gene as the target and a functional eGFP is produced if the gene is repaired; then, the corrected cells express eGFP and display green fluorescence. In the standard model system, a single copy of the eGFP gene with a single base mutation -TAC → TAG -generating a stop codon has been stably integrated in the sequence of HCT116 cells.…”
Section: Recovery and Proliferation Of Genetically Modified Cancer Cellsmentioning
confidence: 99%
“…Indeed, studies in E. coli demonstrated that ssODNs corresponding in sequence to the lagging strand consistently performed better, irrespective of the direction of transcription, thereby establishing a direct link between ssODN polarity and the direction of replication through the target locus. 14,20,21,28,29 In mammalian cells, a direct link between the polarity of the ssODN and the direction of replication could not be established, 16,30 as the direction of the replication fork through the target locus is difficult to determine and may vary because of the firing of different origins in subsequent cell cycles.…”
Section: Mechanistic Models For Ssodn-mediated Gene Targetingmentioning
confidence: 99%
“…Igoucheva et al 31 suggested a model based on the differential accessibility of the DNA strands during transcription to explain the often-observed strand bias in favor of anti-sense ssODNs. 10,11,13,27,30 During transcription, ssDNA regions are provided that facilitates annealing of complementary ssODN. The increased accessibility of the non-transcribed strand could promote annealing of anti-sense ssODNs, whereas the RNA polymerase activity on the transcribed strand could lead to displacement of sense ssODNs.…”
Section: Mechanistic Models For Ssodn-mediated Gene Targetingmentioning
confidence: 99%
See 1 more Smart Citation
“…Some labs have reported different clonal efficiencies after illegitimate integration 22,23 or different efficiencies for point mutations of different mismatches. 12 We sought to systematically probe these two sources of variability.…”
Section: Correction Efficiency Varies With Esc Clonal Line and Ssodn mentioning
confidence: 99%